Chain length affects pancreatic lipase activity and the extent and pH–time profile of triglyceride lipolysis - Benito-Gallo, Paloma; Franceschetto, Alessandro; Wong, Jonathan C.M.; Marlow, Maria; Zann, Vanessa; Scholes, Peter; Gershkovich, Pavel (Elsevier, 2015)
Triglycerides (TG) are one of the most common excipients used in oral lipid-based formulations. The chain length of the TG plays an important role in the oral bioavailability of the co-administered drug. Fatty acid (FA) chain-length specificity of porcine pancreatic lipase was studied by means of an in vitro lipolysis model under bio-relevant conditions at pH 6.80. In order to determine the total extent of lipolysis, back-titration experiments at pH 11.50 were performed. Results suggest that there is a specific chain length range (C2–C8) for which pancreatic lipase shows higher activity. This specificity could result from a combination of physicochemical properties of TGs, 2-monoglycerides (2-MGs) and FAs, namely the droplet size of the TGs, the solubility of 2-MGs within mixed micelles, and the relative stability of the FAs as leaving groups in the hydrolysis reaction. During experimentation, it was evident that an optimisation of lipolysis conditions was needed for tighter control over pH levels so as to better mimic in vivo conditions. 1 M NaOH, 3.5 mL/min maximum dosing rate, and 3 μL/min minimum dosing rate were the optimised set of conditions that allowed better pH control, as well as the differentiation of the lipolysis of different lipid loads.